Republican liberty and compulsory voting - Armin Schäfer (Max Planck Institute for the Study of Societies, 2011)
This paper starts from four observations: (1) voter turnout is declining in established democracies; (2) low turnout means socio-economically unequal turnout; (3) compulsory voting is an effective means to increase turnout; (4) even low-turnout countries, however, have neither introduced nor even contemplated a legal obligation to vote. A closer look at the arguments against compulsory voting shows that these draw on assumptions from liberal political theory, which defines freedom negatively as non-interference. This concept of freedom has been challenged by 'neo-republican' writers who, in the neo-Athenian tradition, understand freedom as 'sharing in self-government' and, in the neo-Roman, as 'non-domination.' Both strands of republicanism attach importance to political participation and, it will be argued, offer reasons to support compulsory voting. The purpose of this paper is to show that opponents to mandatory voting have to rely on liberal assumptions that have not remained uncontested and to outline a republican defense of equal participation. – – Aufgrund von vier Beobachtungen diskutiert das Papier, ob sich eine Wahlpflicht rechtfertigen lässt: (1) In vielen etablierten Demokratien sinkt die Wahlbeteiligung; (2) eine niedrige Wahlbeteiligung ist immer sozial ungleich; (3) eine Wahlpflicht ist ein effektives Mittel, die Wahlbeteiligung anzuheben, aber dennoch (4) gibt es selbst in Ländern mit niedriger Wahlbeteiligung kaum Bestrebungen, Bürger zur Wahlteilnahme zu verpflichten. Argumente gegen die Wahlpflicht stützen sich überwiegend auf Annahmen der liberalen politischen Theorie, in der Freiheit negativ als Abwesenheit von Einmischung verstanden wird. Gegen dieses Freiheitsverständnis wenden sich 'neo-republikanische' Autoren, die in der neo-athenischen Spielart Freiheit als Selbstregierung und in der neo-römischen als Nichtdominierung verstehen. Beide Varianten betonen die Bedeutung politischer Partizipation für die Demokratie und bieten Rechtfertigungsgründe für die Einführung einer Wahlpflicht. Das Papier führt den Nachweis, dass die Gegner einer Wahlpflicht sich auf Annahmen stützen, die nicht unumstritten sind, und entwickelt eine republikanische Verteidigung gleicher politischer Partizipation.
Keywords: 300